Current state of the art in therapeutic management of osteoarthritis - Iva Parvova; Valentina Petkova; Russka Shumnalieva (Pharmacia)
Osteoarthritis is the most frequent rheumatic disease affecting the joints. Recent advances in genetic and biochemical studies reveal the mechanisms behind the degenerative process in OA; however, there is no known compound that can definitively halt the degenerative cascade. Numerous pharmacologic in vitro and animal model studies have been conducted in recent years to assess the efficacy and safety of new chemical and biological agents and plant-derived substances—candidates for novel osteoarthritis drugs. The aim of the study is to present the current state of the art in the therapeutic management of osteoarthritis. Nevertheless, the primary targets of current treatment are pain relief and improvement of joint mobility. Autologous conditioned serum represents a new direction in the development of disease-modifying osteoarthritic drugs for the treatment of knee osteoarthritis. This therapy is a simple, safe, and conservative option with limited adverse effects and few contraindications. Biological approaches, such as the use of human granulocyte colony stimulating factor combined with autologous activated peripheral blood stem cells or platelet-rich plasma, appear to be among the most promising strategies for cartilage recovery. In advanced cases, for patients with osteoarthritis of the knee and hip, arthroplasty is performed.